ILMU PENGETAHUAN DARI JOHN LOCKE KE AL-ATTAS - Izzatur Rusuli; Zakiul Fuady M. Daud (Jurnal Pencerahan, 2015)
Knowledge is something that is very vital in human life, especially in building the civilization of a nation. This study focuses its analysis on how the concept of knowledge and its worldview both from the perspectives of the West and Islam. The results showed that knowledge in the West is a rational idea constructed by individuals based on the empirical experience. The characteristics of knowledge in the perspective of the West is a systematic, objective, general, reliable, and communal. Furthermore, Western knowledge derived from reason and the senses and therefore contributes to the truth that is both realism and idealism that Western knowledge of truth because truth is relative to current knowledge can be aborted by the truth of the knowledge that comes next if deemed no longer relevant. While knowledge in Islam are referred to as "al-‘ilm", meaning the arrival of an active life and creative on the meaning of something that comes from God resulting in truth and reality through the senses, reason and scientific activity. As for the sources of knowledge in Islam there are two; the source of divine and human sources. Divine source consists of three parts; al-Qur'an, al-Sunnah, and intuition (inspiration). While human resources are divided into two; senses and minds. Because the sources of knowledge in Islam are various, then the truth is generated also vary and stratified, i.e., the absolute truth (al-Qur'an), the truth of the original and authentic, but has dual implications (al-Sunnah and inspiration), and truth chances are still open to debate (mind and the senses). Comparison between the Western and Islamic knowledge have an impact on the overall concept of knowledge are summarized in different characters. Western knowledge has the character to be skeptical, rational-empirical, dichotomous, positivistic-objective, and is antimetafisika. While the character of knowledge in Islam is to be relied on spiritual strength (al-Qur'an), the harmonious relationship between revelation with reason, has a theocentric orientation, and the value-bounded.